Circ-PRMT5 promotes gastric cancer progression by sponging miR-145 and miR-1304 to upregulate MYC - Wenbo Du (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Background Gastric cancer (GC) is a global leading source of cancer-associated deaths. Circular RNAs (circRNAs) are a new type of non-coding RNA and promising biomarkers for diagnosis of multiple diseases such as cancer.Methods Circ-PRMT5 expression was validated in 90 GC patient tissues and 6 different GC cells by qRT-PCR. Sublocalization of circ-PRMT5 in GC cells was determined in isolated nuclear and cytoplasmic RNAs. CircInteractome and miRanda were used to predict binding sites between circ-PRMT5 with micRNAs, and micRNAs with target mRNA. The correlation between genes was determined by the Pearson correlation analysis. The molecular mechanism was demonstrated by RNA in vivo precipitation, point mutation, luciferase activity and rescue experiments.Results Circ-PRMT5 expression was significantly higher in GC than in adjacent normal tissues, and GC patients with circ-PRMT5 high expression had shorter survival times. Functionally, circ-PRMT5 silence inhibited GC cell growth and invasion. Mechanism analysis showed that circ-PRMT5 sponged miR-145/miR-1304 to upregulate MYC expression and GC development.Conclusion Our findings demonstrated that circ-PRMT5 function as an oncogene in GC patients by targeting miR-145/miR-1304/MYC axis. High circ-PRMT5 expression may provide a poor prognostic indicator of survival in GC patients and targeting circ-PRMT5/miR-145/miR-1304/MYC axis may be a novel therapeutic strategy for GC.